Prednisolone adsorption on lung surfactant models: insights on the formation of nanoaggregates, monolayer collapse and prednisolone spreading. Issue 9 (17th January 2017) - Estrada-López, Evelina D.; Murce, Erika; Franca, Matheus P. P.; Pimentel, Andre S.
Abstract : The adsorption of prednisolone on a lung surfactant model was successfully performed using coarse grained molecular dynamics. Abstract : The adsorption of prednisolone on a lung surfactant model was successfully performed using coarse grained molecular dynamics. The prednisolone coarse grained model was parameterized using a well-established cholesterol model and validated by using calculations of octanol–water partition coefficients and lateral diffusion coefficients. The calculated octanol–water partition coefficient of prednisolone is 3.9. The lateral diffusion coefficient of prednisolone in the DPPC/POPC mixed monolayer is estimated to be (6 ± 4) × 10 −7 cm 2 s −1 at 20 mN m −1, which is in agreement with that found for cholesterol. The DPPC/POPC mixed monolayer was used as lung surfactant model where prednisolone molecules were adsorbed forming nanoaggregates at surface tension of 0 mN m −1 . The nanoaggregates of prednisolone were transferred into the DPPC/POPC mixed monolayer being spread at the surface tension of 20 mN m −1 . At 0 mN m −1, the prednisolone nanoaggregates induce the collapse of the DPPC/POPC mixed monolayer forming a bilayer. The implications of this finding are that prednisolone may only be administered with lung surfactant by using low fractions of prednisolone per lipid, and with high fractions, the collapse inactivates the properties of the lung surfactant by forming a bilayer that may be eliminated by the clearance process of the lung.